ANALISIS PENGARUH BI RATE, INFLASI, JUMLAH UANG BEREDAR (JUB) TERHADAP CAPITAL ADEQUECY RATIO PADA NON DEVISA PERIODE 2010 SAMPAI 2014 - B2051141023, MARVELLO YANG (Jurnal Ekonomi Daerah (JEDA), 2016)
The purpose of the present study is to explain the influence analysis of BI rate, Inflation and Spread money to the Capital Adequacy Ratio (CAR) of Non Devisa banking in Indonesia period 2010- 2014. Macro economic variables in this research are measured by Bank Indonesia rate, Inflation and Spread money. The most important indicator in evaluating the capital adequacy ratio banking performance  is  Indonesia rate . The data used in this study were obtained from published reported statements of Bank Indonesia. Data analysis techniques used in this study is multiple linier regression analysis.  During research period shows as variables and the data research was normal distributed. Based on test, multicolinearity, heteroskedasticity, and autocorrealation test classic assumption deviation has no found, this indicate that the available data has fulfill the condition to use multi linear regression model. F-statistic at level of significance 5%. F test results showed that simultaneous variable of BI rate, Inflation and Spread money have a significant effect on CAR, 27 % and others explained by other factors.While the results of t test showed that partially, Inflation and spread money has negative and significant influence on CAR, while BI rate has positive and significant influence on CAR. Keywords : BI Rate,  Inflation,  Spread money,  Capital Adequacy Ratio (CAR).